Breaking bad: avoiding the 10 worst IT admin habits. Issue 1 (January 2016) - Fimin, Michael
Abstract : Most experienced system administrators have faced the problem of sorting out an inherited IT infrastructure at least once and have been unsatisfied with the work of a predecessor. It may take a long time to understand the reasons why IT systems are sometimes poorly managed, but this is a reality you have to accept. It's easy to fall into bad habits when administering networks, and the chaos they cause can leave your systems vulnerable to attack. Michael Fimin of Netwrix outlines the most common issues that may hinder organisations from optimising their operations or even fall victim to security incidents. By avoiding the worst pitfalls, administrators can ensure their environments are as robust as possible against outside attack and everyday issues.